Relative concerns of rural-to-urban migrants in China - Alpaslan Akay; Olivier Bargain; Klaus F. Zimmermann (University College Dublin, UCD School of Economics, 2011)
How the income of relevant others affects well-being has received renewed interest in the recent literature using subjective data. Migrants constitutes a particularly interesting group to study this question: as they changed environment, they are likely to be concerned by several potential reference groups including the people left behind, other migrants and natives. We focus here on the huge population of rural-to-urban migrants in China. We exploit a novel dataset that comprises samples of migrants and urban people living in the same cities, as well as rural households mostly surveyed in the provinces where migrants are coming from. After establishing these links, we find that the well-being of migrants is largely affected by relative concerns: results point to negative relative concerns toward other migrants and workers of home regions - this status effect is particularly strong for migrants who wish to settle permanently in cities. We find in contrast a positive relative income effect vis-à-vis the urban reference group, interpreted as a signal effect: larger urban incomes indicate higher income prospects for the migrants. A richer pattern is obtained when sorting migrants according to the duration of stay, expectations to return to home countries and characteristics related to family circumstances, work conditions and community ties.
Keywords: C90; D63; 330; China; relative concerns; well-being